Inclusiveness and ethical considerations for observational, translational, and clinical cancer health disparity research. Issue 24 (10th September 2019) - Behring, Michael; Hale, Kevin; Ozaydin, Bunyamin; Grizzle, William E.; Sodeke, Stephen O.; Manne, Upender
Abstract : Background: Although general trends in cancer outcomes are improving, racial/ethnic disparities in patient outcomes continue to widen, suggesting disparity‐related shortcomings in cancer research designs. Methods: Using convenience sampling, a total of 24 data sources, representing several research designs and 5 high‐burden tumor types, were included for analyses. The percentages of races/ethnicities across each design/tumor type were compared with those of the 2017 US Census data. The authors used a framework based on the Belmont principles to evaluate the ethical strengths and/or weaknesses of each design. Results: In all designs, white individuals were found to be overrepresented. African American and Asian individuals were underrepresented, and Native Americans had consistently poor or no representation. In general, ethical concerns varied according to the study design. Clinical trials were high with regard to respect for persons and beneficence but low for equitable subject selection related to the inclusion of race/ethnicity. Observational study designs were more inclusive for race/ethnicity compared with clinical and translational studies, but their clinical usefulness was less. Conclusions: The authors proposed that ethical concerns should vary according to the study design. Because observational designs have strengths in inclusiveness for race/ethnicity, their clinical usefulness can be improved by extending the Learning Health System in hospital catchment populations, the use of health records linked to biospecimens, and minority oversampling. Likewise, minority enrollment into clinical trials can be improved through Learning Health System linking and by using National Cancer Institute–mandated Community Outreach and Engagement Cores. This will allow precision medicine for otherwise overlooked minority subgroups. Abstract : Study design in cancer research is an inherent contributor to health disparities and inclusiveness. In the current study, the authors report that each design has unique ethical strengths and weaknesses that can serve as targets for improvement.